Effect of the introduction of trade subjects on the senior secondary school economics curriculum and enrolment in Nigeria (2024)
Economics is the most popular subject in the SSS Curriculum in Nigeria. It is offered by nearly all students. However, with the introduction of trade subjects into the SSS Curriculum, the popularity of economics among SSS Students became a point of debate among researchers and Curriculum planners. The researcher therefore, examined the effect this trade subject had on SSS economics enrolment, and the entrepreneurship aspect of Economics and the UTME admission requirement as it relates to Economics and these trade subjects. The study is an expost facto research and it made use of data on enrolment for Economics by public examination bodies, comparison of the curriculum of economics with that of trade subjects as well as JAMB brochure on requirements for admission, in analysing the effects of the introduction of trade subjects on the economics curriculum and enrolment. Three research questions guided the study. Analysing data presented by examination bodies, such as the WAEC and JAMB, the researcher was able to proof that, despite the introduction of trade subjects, Economics still maintain its popularity with students. It also kept its place as having the most comprehensive entrepreneurship topic compared to trade subjects. In addition, compared to trade subjects, Economics is still an important requirement for admission into Nigeria University while trade subjects are rarely required for admission. It is therefore recommended that curriculum planners should, in recognition of the popularity and usefulness of Economics, work on regularly improving/updating the Economics Curriculum, in order to make it attractive to all categories of secondary school students.